2009
DOI: 10.1021/jp811280k
|View full text |Cite
|
Sign up to set email alerts
|

FePt Icosahedra with Magnetic Cores and Catalytic Shells

Abstract: Surprisingly oxidation resistant icosahedral FePt nanoparticles showing hard-magnetic properties have been fabricated by an inert-gas condensation method with in-flight annealing. High-resolution transmission electron microscopy (HRTEM) images with sub-Angstrom resolution of the nanoparticle have been obtained with focal series reconstruction, revealing noncrystalline nature of the nanoparticle. Digital dark-field method combined with structure reconstruction as well as HRTEM simulations reveal that these nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 24 publications
8
57
0
Order By: Relevance
“…The image corresponds to a McKay icosahedral geometry, where the icosahedron is assembled from single crystal tetrahedra with (111) faces [28,32] (see Figure 2c). This type of structure, as previously observed in other fcc metal NPs [22,23,28,33], can be ascribed to the dynamics of NP growth. In particular, it was found that formation of icosahedra is favoured at fast quenching rates for fcc metal NPs [33][34][35].…”
Section: Resultssupporting
confidence: 79%
“…The image corresponds to a McKay icosahedral geometry, where the icosahedron is assembled from single crystal tetrahedra with (111) faces [28,32] (see Figure 2c). This type of structure, as previously observed in other fcc metal NPs [22,23,28,33], can be ascribed to the dynamics of NP growth. In particular, it was found that formation of icosahedra is favoured at fast quenching rates for fcc metal NPs [33][34][35].…”
Section: Resultssupporting
confidence: 79%
“…Current efforts further concentrate on improving permanent hard magnets, which are required for future energy-harvesting technologies 3 , while recently also exchange-spring composites based on soft and hard magnetic nanoparticles have been discussed for advanced applications of permanent magnets 4 . Another example is the combination of catalytic activity with magnetic response 5 . Designing new types of bimetallic multifunctional nanoparticles for all of these applications requires the atomistic understanding of the origin of the particles' magnetism, for example, if it is dominated by the large surface fraction of the atoms in a lower coordinated electronic state or dominated by intrinsic lattice strains.…”
mentioning
confidence: 99%
“…FePt nanoparticles were synthesized by thermal decomposition of Fe(CO) 5 and Pt(acac) 2 as described elsewhere 23 . The particles are in the chemically disordered state as the formation of the chemically ordered state-which is the equilibrium state at room temperature-is kinetically suppressed.…”
mentioning
confidence: 99%
“…Moreover, several experimental studies support the existence of a minimum size limit below which the L1 0 order can no longer be achieved, 51,52 and other studies have shown the migration of Pt atoms towards the surface in smaller particles. 53,54 However, for more definitive answers concerning feasibility of exploiting FePt nanoparticles in the applications mentioned in the Introduction, detailed and systematic studies are in order.…”
Section: Magnetic Anisotropy Of L1 0 Fept Nanoclustersmentioning
confidence: 99%